2003
DOI: 10.1021/la034661w
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Structural and Rheological Response of L3 Sponge Phases in the “Sweetened” Cetylpyridinium/Hexanol/Dextrose/Brine System

Abstract: We report a study of the shear response of sponge phases in cetylpyridinium chloride (CPCl)/hexanol/brine/dextrose systems by parallel measurements of rheology and structure by small angle neutron scattering (SANS). Our measurements show that this dextrose added to the extensively studied CPCl/hexanol/brine system is taken up exclusively by the brine solvent, resulting in an equivalent CPCl/hexanol membrane structure and phase behavior for this modified system. Adding dextrose to the brine in these systems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 57 publications
(84 reference statements)
6
53
1
Order By: Relevance
“…In both phases, these characteristic distances scale inversely to the membrane volume fraction (ϕ) according to swelling laws. 8,24 For the cetylpyridinium chloride (CPCl)− hexanol−brine system, 15,27 the L 3 phase exists over a narrow range of hexanol/CPCl ratios but over a large range of membrane volume fractions with passage sizes ranging from nanometers to a few micrometers. Reducing the hexanol concentration moves the system though a narrow two-phase region (L 3 and L α phases) into the large L α phase, which is similarly stable over a wide range of membrane volume fractions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In both phases, these characteristic distances scale inversely to the membrane volume fraction (ϕ) according to swelling laws. 8,24 For the cetylpyridinium chloride (CPCl)− hexanol−brine system, 15,27 the L 3 phase exists over a narrow range of hexanol/CPCl ratios but over a large range of membrane volume fractions with passage sizes ranging from nanometers to a few micrometers. Reducing the hexanol concentration moves the system though a narrow two-phase region (L 3 and L α phases) into the large L α phase, which is similarly stable over a wide range of membrane volume fractions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…So far, shear-induced phase transitions reported in bilayer-forming amphiphilic systems have shown that an isotropic sponge phase ðL 3 Þ of interconnecting bilayers can transform to a lamellar phase ðL α Þ consisting of a stack of bilayers with 1D quasi-longrange positional order (17) or that a dilute L α phase is sheartransformed to a collapsed surfactant-rich L α phase with very little water between the bilayers, coexisting with excess solvent (18). In this context, the studies have been restricted to the swollen L α or L 3 phase with highly flexible bilayers dominated by steric repulsion, where the transitions occur due to shearinduced suppression of thermal fluctuations above a critical shear rate of _ γ c (19).…”
mentioning
confidence: 99%
“…In this context, the studies have been restricted to the swollen L α or L 3 phase with highly flexible bilayers dominated by steric repulsion, where the transitions occur due to shearinduced suppression of thermal fluctuations above a critical shear rate of _ γ c (19). Because _ γ c ∼ ϕ n , where ϕ is the surfactant volume fraction and the exponent n lies (18) in the range of 1.5-3, the transitions are absent for ϕ > 0.3 within the experimentally accessible range of shear rates (∼1,000 s −1 ) (20). Our present study is different from the earlier studies on sponge phases because it examines the role of steady shear in weakly swollen, concentrated (ϕ > 0.5) isotropic phases (15,21) …”
mentioning
confidence: 99%
“…In light scattering measurements on ''hyperswollen'' C 12 E 5 sponges at membrane volume fractions below 2%, Yamamoto and Tanaka [3] were able to demonstrate that applied shear could induce an L 3 to L transition. Recently we showed that adding an inert thickener, dextrose, to the brine solvent in the widely studied cetylpyridinium(CPCl)-hexanol membrane system significantly slowed membrane dynamics resulting in much stronger responses to applied shear _ [4,5]. The response depends upon a rescaled shear rate parameter, _ s = 3 , where s is the viscosity of the solvent [6].…”
mentioning
confidence: 99%